The crisis of capitalism and the marketization of health care: the implications for public health professionals - Martin McKee; David Stuckler (SAGE Publishing, 2012)
The current economic crisis in Europe has challenged the basis of the economic model that currently prevails in much of the industrialised world. It has revealed a system that is managed not for the benefit of the people but rather for corporations and the small elite who lead them and which is clearly unsustainable in its present form. Yet, there is a hidden consequence of this system: an unfolding crisis in health care, driven by the greed of corporations whose profit-seeking model is also failing. Proponents of commodifying healthcare simultaneously argue that the cost of providing care for ageing populations is unaffordable while working to create demand for their health care products among those who are essentially healthy. Will healthcare be the next profit-fuelled investor bubble? In this paper we call on health professionals to heed the warnings from the economic crisis and, rather than stand by while a crisis unfolds, act now to redirect increasingly market-oriented health systems to serve the common good.